Respon Pertumbuhan Tanaman Porang (Amorphophallus muelleri Blume.) Dengan Penambahan NAA (Naphthalene Acetic Acid) dan BAP (6-Benzyl Amino Purine) Pada Perbanyakan Secara In Vitro - Wardana, Rudi; Arifah, Siti Afivatul; Jumiatun, Jumiatun (Agropross : National Conference Proceedings of Agriculture, 2023)
Porang is one of the export crops that are much hunted in several countries. The increasing number of needs has resulted in limited porang seeds so that there is a need for propagation of porang plants with good quality, one of which is by propagation through tissue culture or in vitro. In order to propagate porang plants in vitro, this research tries to discover the ideal concentration of NAA and BAP. From August to December 2022, this study was conducted in the Plant Tissue Culture Laboratory of Jember State Polytechnic. The experiment employed a parametric statistical design with 2 treatments: 0.5 mg/L NAA + 1.5 mg/L BAP (P1) and 0.5 mg/L + 2.5 mg/L BAP (P2), with each treatment being repeated 10 times. According to the findings, the parameters of callus emergence time (46 HST) and callus diameter (1.51 cm) were best achieved by administering NAA and BAP at a dosage of 0.5 mg/L NAA + 2.5 mg/L BAP. According to the study aims, the optimal concentration for explant growth and development is believed to be 0.5 mg/l NAA + 2.5 mg/l BAP.